Defining Political Extremism in the Balkans. The Case of Serbia - Babić, Marko (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
Political extremism (and particularly right wing political extremism) remains relatively insufficiently explored due to the fact that the phenomenon is controversial and hard to define. Its ambiguity and variability depending on time and spatial point of view further complicates its definition. Its structure is amorphous and eclectic as it often includes elements from different ideologies and connects incompatible ideas. A multidimensional conceptualization and an interdisciplinary approach - sociological, social, psychological and historical, are the Author’s tools in explaining the phenomenon of political extremism in Serbia, hopefully contributing to its clarification and laying a foundation for its further explanatory theoretical studies.